Effect of Frozen Storage on Nutritional Chemical Quality of Shrimp (Exopalaemon Styliferus) from the South of Iraq - Mahdi Hassan Hussain (Journal of Global Pharma Technology, 2019)
The aim of this research is to investigate the influence of frozen storage at -20°C for six month on nutritional chemical quality of shrimp Exopalaemon styliferus that include moisture, PH. protein, fat, volatile basic nitrogen (TVB-N), trimethylamine nitrogen (TMAN), Free fatty acid (FFA) Formaldehyde (FA) content, thiobarbituric acid reactive substances (TBARS) and astaxanthin. Results of present study indicated that values of PH, TVB-N, TMAN, FFA, FA and TBARS were increased with increasing time during frozen storage. However, values of moisture, protein, fat and astaxanthin were decreased during storage.Keywords: Frozen storage, Shrimp, Nutritional quality, TVB-N, TMA, Formaldehyde.